The Use of Multisensory Kit to Reduce Disruptive Behaviour of Student with Autism - Bakar, Nadiah Abu (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
Multisensory Kit is a collection items of sensory tools that can be used to calm and stimulate student’s sensory system. This study aims to examine the use of Multisensory Kit to reduce the disruptive behaviour of Autism student in one of the schools in Kuala Lumpur. This study was conducted during the implementation of the Visual Art subject and involved Autism student who was selected on purpose. The study design was a single-subject design (A-B-A) involving baseline phase (A), intervention phase (B) and non-intervention phase (A), conducted for six consecutive weeks. Researchers have used the Multisensory Kit as an intervention to control the disruptive behaviour of Autism student during the learning sessions. Data were collected and analysed using frequency tables and line graphs adapted from Miltenberger (2001). The findings showed that there were changes in behaviour and students' concentration increased after the intervention. This study is expected to guide and help Special Education teachers to address behavioural issues in the classroom.